Outcome of Myringoplasty with Temporalis Fascia and Perichondrial-Cartilage Composite Graft in High Risk Perforations - Dhungana, Anup; Joshi, RR; Rijal, AS; Shrestha, KK; Maharjan, S (Nepal Medical College Journal, 2019)
The objective of this study was to compare the graft uptake results and postoperative hearing of myringoplasty with temporalis fascia and cartilage-perichondrial composite graft in high risk perforations. Patients of age 13 years and above with diagnosis of chronic otitis media – mucosal type with high risk perforation that is >50% perforation of tympanic membrane, revision cases, absent/ eroded handle of malleus, oedematous/unhealthy middle ear mucosa and marginal involvement cases were included for myringoplasty. Pure Tone Audiometry was done within 1 week before surgery. 80 cases were included for myringoplasty which were randomly allocated by lottery method with 40 cases each in temporalis fascia group and cartilage perichondrial composite graft group. Graft uptake results were assessed after 6 weeks and postoperative hearing was evaluated and compared within and between the groups. Graft uptake rate in temporalis fascia group and cartilage perichondrial composite graft group was 90% and 92.5%, respectively with no significance difference in the graft uptake rate (p = 0.692) between the groups. The mean pre and post-operative air bone gap in temporalis fascia group and cartilage perichondrial composite group were 30.69dB±10.19,16.36±8.37dB and 33.73±8.07dB, 20.76±9.47dB, respectively with highly significant difference in both groups (p < 0.001) showing improvement in the hearing after surgery in both groups. The mean air bone gain were 14.33dB and 12.97dB in temporalis fascia and cartilage perichondrial composite group respectively with no significant difference between the groups (p=0.469). The graft uptake rate and hearing results after cartilage perichondrial composite graft are comparable to those of temporalis fascia graft. Furthermore, the cartilage perichondrial composite graft is more rigid and thick so it is more resistant than fascia to anatomic deformation and necrosis. Therefore, we recommend the use of cartilage perichondrial composite graft for tympanic membrane reconstruction in high risk perforation without concern about affecting audiometric results.